A Macro tool to characterize and develop key competencies for the mathematics teacher’ practice (2022)
RESUMEN: The initial and continuing training of mathematics teachers continues to be one of the most pressing challenges facing the research community in mathematics education. In this regard, various research agendas have been proposed and developed. Among these, two stand out: the characterization and development of (1) didactic and mathematical knowledge that allows the teacher to favor the management of his classes, and (2) skills necessary for professional practice. Although various models have been proposed to attend to each of these agendas separately, there are no models that allow an explicit integration between the notions of knowledge and teacher competence. On the other hand, various studies show the need to have theoretical-methodological tools that operationalize the categories of knowledge and skills proposed by scientific literature. In this article, the didactic-mathematical knowledge (DMK) model is presented as a theoretical-methodological alternative that allows for both the analysis and the development of essential knowledge and skills for the teacher’s professional practice. In addition, it delves into a proposal of categories and subcategories of professional competencies necessary for teaching.